The Intersection of Mitochondrial Replacement Therapy and In-vitro Fertilisation: A Review of Emerging Therapeutic Approaches - Sravya Gudapati; Kamlesh Chaudhari; Manoj Kumar (Journal of Clinical and Diagnostic Research, 2025)
Mitochondrial Replacement Therapy (MRT) is a development in the area of reproductive health, as it provides new possibilities for women who are at risk of transmitting mitochondrial diseases to their offspring. A cell’s powerhouse, known as mitochondria, contains inherited Deoxyribonucleic Acid (DNA) called mitochondrial DNA (mtDNA) and is inherited only through the mother. Changes in specific areas of the mtDNA can lead to severe mitochondrial disorders affecting major bodily processes and might involve metabolic or neurological problems. New In-Vitro Fertilisation (IVF) procedures, incorporated into Pronuclear Transfer (PNT) and Maternal Spindle Transfer (MST), use MRT to transplant mtDNA along with a donor’s mitochondria, thereby reducing the chances of passing on mitochondrial diseases. The advantage of MRT is the ability to minimise mitochondrial diseases, which is achievable through key techniques. However, MRT poses specific technical issues and raises ethical concerns, particularly concerning germline modifications. The following paper examines the clinical, ethical and technical aspects of MRT with regard to IVF compatibility, success rates and resulting health impacts.